2019
DOI: 10.1002/advs.201802136
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Tunable Reduced Graphene Oxide Substrate Maintains Mouse Embryonic Stem Cell Pluripotency

Abstract: Culturing embryonic stem cells (ESCs) in vitro usually requires animal‐derived trophoblast cells, which may cause pathogenic and immune reactions; moreover, the poor repeatability between batches hinders the clinical application of ESCs. Therefore, it is essential to synthesize a xenogeneic‐free and chemically well‐defined biomaterial substrate for maintaining ESC pluripotency. Herein, the effects of structurally tunable reduced graphene oxide (RGO) substrates with different physicochemical properties on ESC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
(115 reference statements)
0
23
0
Order By: Relevance
“…Viral methods of gene transfection are more efficient, despite recent rapid progress in non-viral gene transfection methods. [1][2][3][4][5][6][7][8][9][10] Among what have been tested, recombinant adeno-associated viruses (rAAV) exhibit clear advantages such as low immunogenicity, long-lasting transfected gene expression in various host cells, and non-exogenous DNA insertion into the genomes of transfected cells. 3 This viral vector has been used in the gene therapy studies of auditory system in animal models [11][12][13][14][15] and human trials.…”
Section: Introductionmentioning
confidence: 99%
“…Viral methods of gene transfection are more efficient, despite recent rapid progress in non-viral gene transfection methods. [1][2][3][4][5][6][7][8][9][10] Among what have been tested, recombinant adeno-associated viruses (rAAV) exhibit clear advantages such as low immunogenicity, long-lasting transfected gene expression in various host cells, and non-exogenous DNA insertion into the genomes of transfected cells. 3 This viral vector has been used in the gene therapy studies of auditory system in animal models [11][12][13][14][15] and human trials.…”
Section: Introductionmentioning
confidence: 99%
“…With the hydrophilicity of GO NPs decreasing, the carbon-to-oxygen ration increases, which probably affects its solubility and toxicity. 44 In our study, GO NPs of approximately 5 µm size exhibited higher cytotoxicity than other GO NPs at concentrations of 100 μg/mL, possibly because of greater coverage of the cell surface leading to nutrient deficiency and more oxidative stress-induced apoptosis. Several studies have demonstrated that the fate of theNSCs is determined by both the internal genes and exogenous signals.…”
Section: Discussionmentioning
confidence: 48%
“…For drug delivery applications, the GO can achieve strong interaction with anti-cancer drugs and shows sensitive response to pH value, thermal and photothermal signals, enabling large amount drug loading, controllable releasing, target delivery, and biodegradation. Besides, GO and its hybrids have been widely used as scaffolds for culturing human mesenchymal stem cells; [96][97][98] the GO-based robotic structures may find practical applications in tissue engineering. Soon, triggered by the sensitive moisture responsiveness of the GO actuators and its potential importance to soft robotics, it is expected that increased research efforts would be devoted to this field, leading to breakthroughs in both fundamental science and practical applications.…”
Section: Discussionmentioning
confidence: 99%